2016
DOI: 10.1161/strokeaha.115.011242
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Location Is an Independent Predictor of Cognitive Outcome

Abstract: Background and Purpose-On top of functional outcome, accurate prediction of cognitive outcome for stroke patients is an unmet need with major implications for clinical management. We investigated whether stroke location may contribute independent prognostic value to multifactorial predictive models of functional and cognitive outcomes. Methods-Four hundred twenty-eight consecutive patients with ischemic stroke were prospectively assessed with magnetic resonance imaging at 24 to 72 hours and at 3 months for fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
105
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 39 publications
9
105
1
3
Order By: Relevance
“…Our results align with findings in the literature. Munsch et al 27 identified stroke location as an independent determinant of cognitive outcome as measured at 3 months post-stroke. Similar results were demonstrated by Wu et al 28 , highlighting the importance of joint modelling of DWI volume and topography for stroke outcomes, while our approach also takes network topology into account.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results align with findings in the literature. Munsch et al 27 identified stroke location as an independent determinant of cognitive outcome as measured at 3 months post-stroke. Similar results were demonstrated by Wu et al 28 , highlighting the importance of joint modelling of DWI volume and topography for stroke outcomes, while our approach also takes network topology into account.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted attacks on their connections can have a significant impact on global network efficiency 8 and have been shown to lead to functional deficits in disorders like Alzheimer's disease 26 . Importantly, stroke location has been identified as an independent determinant of cognitive outcome 27,28 , in addition to widely accepted clinical factors, such as age 29 and stroke lesion size 30,31 . Furthermore, a strong coupling between brain hubs, especially those lying in the cerebral cortex, and regional blood flow has been unveiled during rest as well as in response to task demands 32 .…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, lesion volumes have shown only moderate correlation with long-term clinical outcome measures 2 . Recent studies 5,7,28,29 demonstrated that models taking into account accurate lesion topography (in addition to lesion volume) improve stroke prediction outcome and identify patients likely to benefit most aggressive reperfusion intervention and personalized rehabilitation therapies. Indeed, when deciding whether to perform reperfusion therapy, it is important to confirm whether the lenticulostriate arteries are involved in the ischemia 16,30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Ведущую роль в генезе КН играет не объем инфаркта или кровоизлияния, а поражение стратегических для когни-тивных функций областей головного мозга [12,13]. Постин-сультные КН бывают вызваны не только очаговым сосуди-стым поражением головного мозга, но и наличием сопутст-вующих сосудистых и дегенеративных либо других пораже-ний, которые могут усилиться (декомпенсироваться) после развития инсульта [1,2,14].…”
Section: неврология нейропсихиатрия психосоматика 2018;10(1):37-42unclassified